ХУДОЖЕСТВЕННЫЙ ПСИХОЛОГИЗМ ДО И ПОСЛЕ ФРЕЙДА: (русский и зарубежный опыт) (Filološke pripombe, 2019)
In the essay the author shows that the World Literature of the XIX – XX centuries in many ways predicts some Freud’s discoveries in the fields of psychoanalysis, unconsciousness, dreams, and was passionately looking for adequate literary forms and means to depict these things. The author appeals to the artistic works of the Western and Russian writers while advancing his thesis.